Innate Immune Control of Adipose Tissue Homeostasis. Issue 9 (September 2019) - Kane, Harry; Lynch, Lydia
Abstract : Adipose tissue is a critical regulator of systemic metabolism and normal bodily homeostasis. Recently, the immune system has been implicated in the regulation of adipose tissue homeostasis and function. Here, we highlight new insights into the distinct phenotypes and functions of adipose resident leukocytes, including a growing body of work on their role in adipose tissue remodeling and thermogenesis. We discuss how the protective capacity of the adipose immune system can be diminished during obesity, where immune cells promote sterile inflammation leading to insulin resistance. Understanding the role of adipose immune cells across different physiological states and processes is important in understanding the full breadth of adipose immunity and the possibilities to harness immune cells in fat tissue for the treatment of chronic metabolic conditions, including obesity. Highlights: The human and murine adipose immune system is enriched in innate immune cells, including innate lymphoid cells and unconventional T cells such as invariant natural killer T (iNKT) cells, γδ T cells, and mucosal-associated invariant T (MAIT) cells (humans). Many of these cells are tissue resident with little recirculation occurring between adipose and peripheral populations. Adipose immune cells have atypical phenotypes adapted to the unusual, lipid-rich adipose environment. Many immune cells express genes associated with lipid handling and metabolism, such as peroxisome proliferator receptor (PPAR)γ, and display alternative or regulatory polarization; for example, adipose iNKT cells produce interleukin (IL)-10 and IL-2 rather than interferon (IFN)γ and IL-4 after stimulation. In mice, the adipose immune system plays a crucial role in maintaining local homeostasis and contributes to the regulation of systemic metabolism. It also performs many noncanonical functions, such as regulating adaptative thermogenesis. In murine and human obesity, the adipose immune system becomes dysregulated. Many of the resident regulatory populations become depleted and are replaced by inflammatory cells as a result of phenotypic switching of resident adipose immune cells or the infiltration of more inflammatory immune cells from the periphery.